Varpha-K Prototype: Evolution of Anticoagulant Treatment with Improved Safety and Efficiency (Global Journal of Medical Research, 2024)
Pharmaceutical chemistry seeks to discover and develop new chemical molecules that can be useful as medicines, in addition to the possibility of improvement in some molecular physicochemical aspect. These modifications cannot alter the pharmacophoric group, which is the chemical functional group responsible for the therapeutic effects (KOROLKOVAS 1982). Thus, our objective was to present the physicochemical aspects related to the association of vitamin K with warfarin molecule (VAR), in order to develop the Varfa-K Prototype, a new drug that has fewer toxic effects, mainly reducing bleeding events caused by VAR. Therefore, we used the methodology of molecular association and insertion of bulky groups. By adding a molecule (vitamin K) to the parent drug and its own antidote against bleeding.
Keywords: drug; disposal; pharmaceutical chemical residues; environment